Seasonal trends in making Domiati cheese from buffalos milk - AL-Ahwall, R. I. H.; Naiem, M. A.; Mehanna, N. M.; El-Shora, M. A. (2003)
The present study was undertaken to define the seasonal changes in the efficiency of making Domiati cheese hat from buffalo's milk collected during smnmer and winter seasons. Analysis of Cheese milk revealed that summer milk (SM) was significantly differed as compared to winter milk (WM). It characterized by higher values for acidity, TS and fat and lower values for pH and protein as well as lower stability to ethanol and rennin (faster RCT). Values of curd tension and curd syneresis were significantly higher in case of SM.
Includes references.
Summary in Arabic.
1
Keywords: Cheese industry; Buffaloes -- Milk yield; Domiati cheese